‘O que o feminismo tem a ver com o dia da mulher?’: Ressignificações do discurso sobre movimentos feministas por meio da interatividade em comentários de notícias no site de rede social facebook - Santos, Janaína Aline (2018)
The historic construction of the feminist movement occurred in a constant process of redetermination in witch meanings and behaviors was negotiated, discussed and fought within the feminist movement, as well in shock with society and its conterspeech that aimed at combating feminist discourse. With the increasing use of social networking sites, its uses expand to become a platform for reading news, as well as for social mobilizations among its varied uses and purposes. The Social Network site Facebook, as others, has become an important media for news. However, it has its particularities, mainly by allowing content to be submitted concurrently with a feedback forum that also re-signifies the content being served. Being a political minority such as women, these discourses can become potentially problematic by allowing a forum of free speech and interactive clashes that can also act to re-signify news and build discourses on feminism. When news about feminist movements is published, how the shock between the speeches present in the news comment boxes posted on Facebook re-signifies the discourses on the feminist movement? In order to verify this dynamics of re-signification in the interactions of the comments on the social network site, the research verified the postings of five vehicles (O Globo, Folha de S. Paulo, O Estado de S. Paulo and A Tarde) during International Women's Day of the year 2017 and 2018 and a sample of their respective comments. The methodology was based on the content analysis of Laurence Bardin (2016) and the critical discourse studies of Teun Van Dijk (2017).